2013
DOI: 10.1016/j.ijpsycho.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Saliency or template? ERP evidence for long-term representation of word stress

Abstract: The present study investigated the event-related brain potential (ERP) correlates of word stress processing. Previous results showed that the violation of a legal stress pattern elicited two consecutive Mismatch Negativity (MMN) components synchronized to the changes on the first and second syllable. The aim of the present study was to test whether ERPs reflect only the detection of salient features present on the syllables, or they reflect the activation of long-term stress related representations.We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 29 publications
6
65
2
Order By: Relevance
“…Meanwhile, it has been shown that stable initial memory representations disabled learning transfer between different memory tasks 57 . The long-term impact of the primarily acquired statistical structure and its predictive power have also been demonstrated in the perception of the auditory environment 58, 59 and in processing native and non-native phonetic features of word stress 60 as indicated by event-related brain potentials (e.g., the mismatch negativity). In line with the previous studies, our results suggest the more influential role of the primarily learnt statistical structure.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it has been shown that stable initial memory representations disabled learning transfer between different memory tasks 57 . The long-term impact of the primarily acquired statistical structure and its predictive power have also been demonstrated in the perception of the auditory environment 58, 59 and in processing native and non-native phonetic features of word stress 60 as indicated by event-related brain potentials (e.g., the mismatch negativity). In line with the previous studies, our results suggest the more influential role of the primarily learnt statistical structure.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, whereas an mmn may be elicited by a purely acoustic difference, many studies will additionally switch the position of the deviant stimulus and the standard stimulus, such that they have another condition, wherein the deviant is presented frequently, while the (formerly) standard stimulus is presented infrequently (e.g. Honbolygó & Csépe, 2013; Aguilera et al, 2014; Scharinger et al, 2016, see also Astésano et al in prep ). If the standard and deviant stimuli differ only acoustically, the mmn s in both conditions should be similar.…”
Section: Introductionmentioning
confidence: 99%
“…Eulitz & Lahiri, 2004; Näätänen et al, 2007; Winkler et al, 2009; Deguchi et al, 2010; Ylinen et al, 2016; Scharinger et al, 2016, 2017), as well as the phonological representation of stress patterns (e.g. Ylinen et al, 2009; Honbolygó et al, 2004; Honbolygó & Csépe, 2013; Aguilera et al, 2014; Honbolygó et al, 2017; Garami et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations